Effect of nutritional education on serum potassium level in patients receiving haemodialysis - Çavdar, Mehmet; Şahin, Habibe (Progress in Nutrition, 2021)
Background: The most effective and practical way to prevent hyperpotassemia, which is an important problem in patients receiving haemodialysis, is to limit potassium intake with diet. One of the most effective methods to be applied for this purpose is nutrition education. Objective: This study was aimed at investigating the effect of nutrition education given to patients receiving haemodialysis with hyperpotassemia on serum potassium levels. Methods: The study was conducted as a prospective intervention study. A total of sixty-eight participants over the age of 18, who received at least three haemodialysis sessions per week for more than six months, and whose serum potassium level was above 5.5 mEq/L were recruited in the study. Intervention: The participants in the intervention group (n=34) were given nutrition education and a handbook including information about potassium in haemodialysis treatment. No nutrition education was given to the participants in the control group (n=34). Results: The comparison of the pre- and post- nutrition education serum potassium levels and the mean potassium knowledge score of the participants in the intervention group demonstrated that while their serum potassium levels decreased significantly, their potassium knowledge score increased (p <0.05). In the control group, no difference was determined between the participants’ pre- and-post study serum potassium levels and potassium knowledge scores (p> 0.05). Conclusions: It was observed that the nutrition education given to patients receiving haemodialysis was effective in lowering the serum potassium levels of the participants